Cyclic Dipeptides Formation From Linear Dipeptides Under Potentially Prebiotic Earth Conditions - Guo, Yeting; Ying, Jianxi; Sun, Dongru; Zhang, Yumeng; Zheng, Minyang; Ding, Ruiwen; Liu, Yan; Zhao, Yufen (Frontiers in Chemistry, 2021)
Cyclic dipeptides (DKPs) are considered as peptide precursors and chiral catalysts in the prebiotic process. Here we report proline-containing DKPs spontaneously obtained from linear dipeptides under aqueous solution. Significantly, the yields of DKPs were affected by sequence of linear dipeptides and whether reaction contains trimetaphosphate. These findings provide the possibility that DKPs might play a key role in the origin of life.